2021
DOI: 10.3389/fpubh.2021.641605
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators for Mental Health Service Use Among Racial/Ethnic Minority Adolescents: A Systematic Review of Literature

Abstract: Introduction: Mental disorders represent serious public health concerns in the U.S. Compared with Whites, racial/ethnic minority adolescents are more likely to be affected by mental disorders but less likely to use mental health services. This systematic review aimed to summarize factors related to mental health service use among minority adolescents in the U.S. as identified in previous research.Methodology: Following the PRISMA guideline, we systematically searched seven databases for peer reviewed articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 60 publications
7
40
0
4
Order By: Relevance
“…Indeed, research shows that young people from low socioeconomic backgrounds are more likely to experience mental health problems [ 1 ], and in turn, statistics show that minoritised ethnic groups are more likely to be classified in lower socioeconomic status that those who identify themselves as white [ 41 ]. This may suggest that black and minoritised ethnic young people experience specific barriers to seeking mental health services, relating to various intersecting types of disadvantage [ 42 , 43 ]. In the present study, it may be that young people from minoritised ethnic groups felt more comfortable engaging in an internet-based therapy where their own, and their therapist’s, ethnic identity is undisclosed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research shows that young people from low socioeconomic backgrounds are more likely to experience mental health problems [ 1 ], and in turn, statistics show that minoritised ethnic groups are more likely to be classified in lower socioeconomic status that those who identify themselves as white [ 41 ]. This may suggest that black and minoritised ethnic young people experience specific barriers to seeking mental health services, relating to various intersecting types of disadvantage [ 42 , 43 ]. In the present study, it may be that young people from minoritised ethnic groups felt more comfortable engaging in an internet-based therapy where their own, and their therapist’s, ethnic identity is undisclosed.…”
Section: Discussionmentioning
confidence: 99%
“…Participants wanted mental health services to be offered through the diabetes clinic and emphasized the need for greater support to obtain services outside the clinic. This may be particularly critical for youth from Hispanic/Latinx backgrounds, who may face greater barriers to accessing mental health services 37 . At a minimum, adolescents and their caregivers need their clinic to provide referrals to trusted mental health professionals who have experience with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly critical for youth from Hispanic/Latinx backgrounds, who may face greater barriers to accessing mental health services. 37 At a minimum, adolescents and their caregivers need their clinic to provide referrals to trusted mental health professionals who have experience with diabetes. Mothers felt a background in diabetes was very important; yet, only half of mental health professionals working in integrated pediatric diabetes care settings report formal training in the medical management of diabetes.…”
Section: Families Of Youth With T1d May Need Support Connecting To Me...mentioning
confidence: 99%
“…In addition to provider shortages, transportation remains one of the largest barriers to accessing behavioral health treatment for children and adolescents, 9 especially for those living in rural areas where families typically travel long distances to get to the nearest behavioral health clinic. Another deterrent for seeking treatment is time, as it is often difficult for parents/guardians to leave or miss work to take their child to appointments 10 . Stigma attached to behavioral health concerns remains a barrier, particularly for some racial and ethnic groups, which limits the number of people seeking care for their children 11 .…”
Section: Barriers To Behavioral Health Treatment For Children and Ado...mentioning
confidence: 99%
“…Another deterrent for seeking treatment is time, as it is often difficult for parents/guardians to leave or miss work to take their child to appointments. 10 Stigma attached to behavioral health concerns remains a barrier, particularly for some racial and ethnic groups, which limits the number of people seeking care for their children. 11 A study among parents in rural areas seeking behavioral health services for their children found that stigma led to decreased willingness to seek services from settings like behavioral health centers.…”
mentioning
confidence: 99%